Optimal Taxation in a Stochastic Endogenous Growth Model with Congestion - Ingrid Ott; Susanne Soretz (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
In this paper the impacts of income and consumption taxes are analyzed within a model of stochastic endogenous growth with congestion. It is shown that the optimal amount of governmental input diminishes with uncertainty and that the optimal financing depends on the relation between the degrees of rivalry and relative risk aversion. Due to the insurance effect associated with the taxation of stochastic income flows, the growth effect of taxation is ambiguous. There is a continuum of optimal tax policies which depends on the assumptions about the governmental budget constraint. The results for a balanced budget are contrasted with the outcomes in the setting with government debt. We demonstrate that in both cases the optimal structure of financing government expenditure not only depends on the degree of rivalry, as in the corresponding deterministic congestion models, but also on the degree of risk aversion.
Keywords: D8; D9; H2; O4; 330; Endogenous Growth; Congestion; Uncertainty; Taxation